Characteristics of solitary wave in fiber bragg grating - Zainudin, Mardiana Shahadatul Aini (2012)
In this study, nonlinear parameters are characterized in terms of the potential energy. This study investigates the photon energy of soliton propagating in a fiber Bragg grating (FBG). The formation of potential well of bright soliton in FBG is performed under Bragg resonance condition. In the presence of Kerr- nonlinearity, using the coupled-mode theory, the nonlinear coupled mode equation is defined. The existence of bright soliton is simulated in the FBG. This is done by applying the equation of bright soliton to the potential well. The results are obtained using MatLab software version R2010a. The nonlinear parameter in this study is initially set to ? = 1.0, ? = 0.7 and ? = 0.1. The simulation of potential energy distribution throughout the grating is examined by varying the value of nonlinear parameters of ?. The changes of nonlinearity parameter depends on the motion of photon in the potential well. This influences the existence of bright Bragg soliton in FBG. The couple mode theory and Stokes parameter provide important information on the total energy and energy differences between the forward and backward propagating modes. The propagation of pump signal and probe signal is investigated in order to monitor photon trapping with soliton. By applying Split Step Method on nonlinear Schrodinger equation (NLSE), the input and output pulse of the wave are obtained for different Fast Fourier Transform (FFT), window size and step size. The associated Legendre equation is applied to the probe equation and solving soliton interaction equation. From the photon trapping profile, it is shown that photon can be trapped in certain time by soliton.